DEVELOPMENT OF PROTEIN ENRICHED GLUTEN FREE KODO MILLET MUFFINS INCORPORATED WITH CHICKEN MEAT POWDER - S. Madesh; P. Sivakumar; Rita Narayanan; V. Nithyalakshmi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The increasing demand for nutritious, gluten-free food options necessitates the development of innovative products. Many commercially available millet-based products fail to leverage the nutritional benefits of millets, incorporating them in minimal quantities while maintaining refined wheat flour (maida) as the primary ingredient in baked goods. This research aims to develop a Kodo millet muffin formulated entirely from Kodo millet flour and enriched with animal protein through the addition of chicken meat powder (CMP). The CMP was prepared and its inclusion level was optimized by varying from 0% to 20% in increments of 5%, based on sensory evaluation using a 9-point hedonic scale. The formulation containing 10% CMP was identified as the most acceptable. The optimized muffins were then analyzed for their textural, physicochemical and nutritional properties. The incorporation of CMP significantly affected the muffin’s texture. This Kodo millet-based, protein-enriched muffin offers a gluten-free alternative while maximizing the health benefits associated with Kodo millet.